Quantitative Analysis of Functional Components From Nelumbo Nucifera Root Fermented Broth with Antioxidant and Tyrosinase Inhibitory Effects. Issue 2 (26th January 2016) - Shukla, Shruti; Lee, Jong Suk; Park, Juyeon; Hwang, Dong‐Ju; Park, Jung Hyun; Kim, Myunghee
Abstract: The goals of this study were to develop a new functional beverage and/or syrup from Nelumbo nucifera (lotus) root by fermentation utilizing brown sugar and to determine its various functional properties and nutritive components. Total phenolic and flavonoid contents significantly increased after 15 and 30 days of fermentation as compared to control (brown sugar broth only) and their amounts ranged from 41–521 µg gallic acid equivalents/mL to 31–63 µg quercetin equivalents/mL, respectively. Gas chromatography‐mass spectra analysis determined the presence of 2‐furanacetic acid, 4‐hydroxyphenyl ethanol, lyxofuranose, silane, morpholine, and cinnamic acid as major phenolic compounds in lotus root sugar syrup samples after 180 days of fermentation. All tested fermented lotus root sugar syrup samples showed highest functional activities in a time‐dependent manner, including inhibition of diphenylpicrylhydrazyl and nitrite radicals (at pH 1.2) as well as superoxide dismutase‐like activities (87.24 ± 2.89%, 99.51 ± 0.67% and 44.39 ± 1.96%, respectively). Syrup samples also inhibited tyrosinase enzyme activity in vitro by 49.79 ± 2.24% compared with control (15.13 ± 0.12%). These findings suggest that lotus root fermented sugar syrup could be a natural food supplement of bioactive components with potent antioxidant and antityrosinase effects. Practical Applications: Plant‐based functional foods show enormous potential as human health supplements. Foods rich in polyphenolic compounds such as phenolics and flavonoids can act as scavengers of free radicals, thus protecting the human body from oxidative stress caused by reactive oxygen species. Lotus ( Nelumbo nucifera ) has been used in traditional medicine system as a health beneficial supplement. Fermentation has been shown to improve the nutritional and medicinal potentials of plants and/or vegetables for human use. This study confirmed fermentation of lotus root using brown sugar, resulting in the production of a fermented functional beverage with enhanced bioactivity. The fermented beverage rich in various nutritional components, including phenolic sand flavonoids, showed potent pharmacological effects such as antioxidant and antimelanogenesis activities, suggesting it might be considered as a good functional food supplement.